Severely reduced physical performance is already present at the time of admission for stem cell transplantation - Dirk Reinhardt; Ronja Beller; Gabriele Gauß; Oliver Basu; Stefan Schönberger; Michaela Höfs (BMJ Open Sport & Exercise Medicine)
Objectives Paediatric patients with cancer undergoing allogeneic haematopoietic stem cell transplantation (allo-HSCT) face a high risk for life-threatening infections and transplant-related complications. Therefore, these children should be in the best possible physical condition beforehand. The study aims to evaluate the fitness status before allo-HSCT and identify correlations between fitness, quality of life and fatigue, clinical data, and previous exercise sessions.Methods Paediatric patients with cancer ≥4 years old, treated with allo-HSCT, were recruited for the ANIMAL trial ('Effects of a low vs. moderate intense exercise program on immune recovery during paediatric allo-HSCT.', DRKS ID:DRKS00019865). Assessed at admission for HSCT were (1) clinical and anthropometric data, (2) motor performance (strength, endurance and balance) and (3) psychological parameters. Values were compared with published reference values (normative data from the literature) of healthy children, and correlation analyses were conducted.Results 22 paediatric patients undergoing pre-allo-HSCT (23% female, 9.4±4.5 years, 73% leukaemia) exhibited substantial reduced differences in all motor performance parameters, with up to −106%±98 (mean difference to reference value) in static stance, −37%±45 in sit-to-stand, −52%±16 in leg extension and −48%±22 in hand grip strength compared with reference values. Correlations were observed among age and fitness parameters, the number of inpatient days and fatigue, and many previous exercise sessions correlated with better hand grip strength.Conclusion These results indicate a poorer fitness status in children before HSCT compared with healthy children, recommending the need for structured exercise programmes for children undergoing HSCT. Differently directed correlations between age/body mass index and endurance/strength and between exercise sessions and strength show the importance of individualised training recommendations and the effect of training.